NILAI-NILAI PENDIDIKAN AGAMA ISLAM PADA TRADISI NYADRAN DI DESATRAJI KECAMATAN PARAKAN KABUPATEN TEMANGGUNG JAWA TENGAH - Muhammad Saefullah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2018)
Islam is a religion of grace for the universe, of course we as Muslims are obliged to makeIslam as a tool in social life, because the habits or norms that are formed in society arenot in accordance with Islamic teachings that we believe to be true. For this reason, it isdeemed necessary to orientate Islamic teachers, which are indeed things that are doneby a Muslim, which indeed cannot be separated from translation as a form of extractingIslamic teachings in understanding them. The rest need methods that are in accordancewith those used in understanding Islamic Education Values in society. In this study theresearchers wanted to know the purpose of implementing the tradition in Traji Villagewith a focus on research on the Nyadran ritual in Traji Village. In collecting this dataresearchers used the method of observation, interview, documentation, questionnaire,and analysis of data with percentages. The population taken in the research was allTraji villagers, while the researchers only took a few to become samples consisting ofcommunity leaders, hamlet devices, parents and youth. From the results of this study it canbe obtained data that the purpose of the Nyadran ritual is to be grateful for the provisionof water sources, to request that the entire community of Traji be given safety, health andabundant food, maintain ancestral heritage and establish a sense of brotherhood betweenthe residents of Traji Village.